1991
DOI: 10.1111/j.1471-0528.1991.tb15401.x
|View full text |Cite
|
Sign up to set email alerts
|

Colposcopically directed punch biopsy: a potentially misleading investigation

Abstract: Objective— To determine the relation between the histology of an initial colposcopically directed punch biopsy and a subsequent diathermy loop excision biopsy of the transformation zone, and the effect of lesion size on this relation. Design— Prospective observational study of loop diathermy excision biopsies of the cervical transformation zone. Setting— Academic unit colposcopy clinics at The Birmingham and Midland Hospital for Women and Dudley Road Hospital, Birmingham. Subjects— 243 women managed by colposc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
50
1
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 4 publications
7
50
1
2
Order By: Relevance
“…Unfortunately, colposcopy shares some of the shortcomings of the Pap smear. Because it is a qualitative assessment of the cervix, its accuracy is dependent on the training and experience of the physician [3]. Several studies have reported that colposcopically directed cervical punch biopsies have a false negative rate ranging from 15 to 31%.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, colposcopy shares some of the shortcomings of the Pap smear. Because it is a qualitative assessment of the cervix, its accuracy is dependent on the training and experience of the physician [3]. Several studies have reported that colposcopically directed cervical punch biopsies have a false negative rate ranging from 15 to 31%.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental to such a management strategy is the assumption that the colposcopist can identify accurately the area of most severe epithelial abnormality from which to take a punch biopsy. 16 Colposcopic assessment is thus a critical stage in the diagnosis of early cervical neoplasia, as the detection of abnormal cervical cytology is dependent on precise visual localisation of micropathological changes and precise biopsy of such tissue for subsequent histopathologic diagnosis. Colposcopy thus plays a crucial role in the diagnosis of early cervical disease, with management decisions often anchored on the colposcopic assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Ehsani et al 12 , após avaliarem mulheres submetidas à CAF por citologia compatível com NIC 2 e 3 e resultado de biópsia sugestivo de NIC 1, encontraram lesão de alto grau em 41% dos cones, indicando o resultado falso-negativo da biópsia. Buxton et al 13 , avaliando 243 mulheres submetidas à conização e com citologias com alterações celulares graves, encontraram discordância em 54%, e com lesão mais grave no cone, em 47% dos casos, incluindo três adenocarcinomas in situ e um caso de câncer invasor.…”
Section: Discussionunclassified